2006
DOI: 10.1111/j.1471-4159.2006.03708.x
|View full text |Cite
|
Sign up to set email alerts
|

Human retinoic acid receptor‐related orphan receptor α1 overexpression protects neurones against oxidative stress‐induced apoptosis

Abstract: Retinoic acid receptor-related orphan receptor a (RORa) is a transcription factor belonging to the superfamily of nuclear receptors. Disruption of the Rora gene in the mouse results in a defect in the development of Purkinje cells leading to a cerebellar atrophy, which suggests a neuroprotective role for RORa. To test this hypothesis, the survival rate of lentiviralmediated human RORa1-overexpressing neurones has been evaluated in response to different stressors disturbing the redox homeostasis, such as b-amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 73 publications
(73 reference statements)
7
65
1
Order By: Relevance
“…The increase in susceptibility to hypoxia was therefore not due to changes in neuronal development in vitro. Moreover, this cell-autonomous function of ROR␣ in neurons was not associated with a deregulation of antioxidant gene expression, contrary to what was previously shown with other stress (Boukhtouche et al, 2006). The target genes of ROR␣ responsible for modulating neuronal survival after hypoxia have yet to be identified.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…The increase in susceptibility to hypoxia was therefore not due to changes in neuronal development in vitro. Moreover, this cell-autonomous function of ROR␣ in neurons was not associated with a deregulation of antioxidant gene expression, contrary to what was previously shown with other stress (Boukhtouche et al, 2006). The target genes of ROR␣ responsible for modulating neuronal survival after hypoxia have yet to be identified.…”
Section: Discussioncontrasting
confidence: 49%
“…The principal CNS phenotype of this mouse is extensive cerebellar neurodegeneration resulting in severe ataxia (Gold et al, 2007). In addition to its function in the cerebellum, ROR␣ has other important functions in the CNS including a neuroprotective role in cortical neurons (Boukhtouche et al, 2006). The upregulation of ROR␣ expression during hypoxia and its neuroprotective function raise questions about the possible role of neuronal and/or astrocyte ROR␣ in neuroprotective mechanisms during hypoxia in the cortex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether an increased RORα expression could be neuroprotective, we have recently developed a recombinant lentiviral vector to perform RORα overexpression in cultured neurons. The survival rate of RORα-overexpressing cortical neurons was evaluated in response to different stressors disturbing redox homeostasis, such as Aß peptide, c 2 -ceramide and H 2 O 2 (51). In this study, we have shown that lentiviral-mediated hRORα1-overexpression provides neuroprotection against reactive oxygen species (ROS)-induced apoptosis.…”
Section: Proliferative and Neuroprotective Function Of Rorα In Thmentioning
confidence: 91%
“…Down-regulation of Gpx1 or Prx6 by si-RNA experiments partially suppressed the RORα-mediated neuroprotection, further demonstrating that this protection is, at least in part, mediated by an up-regulation of the anti-oxidant enzymes glutathione peroxidase 1 and peroxiredoxin 6, which leads to a decrease of the oxidative stress in neurons. RORα appears thus as a factor controlling the oxidative stress in neurons (51).…”
Section: Proliferative and Neuroprotective Function Of Rorα In Thmentioning
confidence: 99%